Are Fiscal Adjustments Bad for Investment? - Christoph A. Schaltegger; Martin Weder (Center for Research in Economics, Management and the Arts (CREMA), 2010)
The current debt crisis in many OECD countries calls for adequate strategies in budget consolidation. To regain fiscal solvency many governments base their fiscal adjustments at least partly on spending cuts. A common political claim is that spending cuts rely too much on investment thereby undermining future long-term growth perspectives. We study the effect of fiscal adjustments on economic growth, consumption and investment for a panel of 20 OECD countries during the 1970-2008 period. Our results support the idea of expansionary consolidations in the case of sizeable adjustments and through spending cuts. The effect is primarily a result of increased consumption rather than investment. While fiscal adjustments also boost private investment, this tends to be offset by a corresponding reduction in government investment. Fiscal consolidations therefore hardly affect total investment.
Keywords: E61; E63; H61; 330; fiscal policy; fiscal adjustment; non-Keynesian effects; investment